Draft Genome Sequence of Uncultivated Desulfosporosinus sp. Strain Tol-M, Obtained by Stable Isotope Probing Using [(13)C(6)]Toluene - Abu Laban, Nidal (Genome Announc, 2015)
A draft Desulfosporosinus genome was assembled from the metagenome of a methanogenic [(13)C(6)]toluene-degrading community. The Desulfosporosinus sp. strain Tol-M genome is distinguished from that of previously published Desulfosporosinus strain by containing bss, bbs, and bam genes encoding enzymes for anaerobic biodegradation of monoaromatic hydrocarbons and lacking dsrAB genes for dissimilatory sulfate reduction.